Famine: causes, prevention, and relief - Mellor, John W.; Gavian, Sarah (American Association for the Advancement of Science, 1987)
Famines are generally caused by decline in food production in successive years brought about by poor weather, war, or both. The consequent complex interactions between prices, employment, and assets impoverish victims and lead to sharply increased mortality. Government policy is a key determinant as to whether or not these conditions mature into widespread famine. India and Bangladesh have succeeded in controlling famines in recent years, but problems in most of Africa remain intractable due to civil unrest and a paucity of resources, including trained people, institutions, and infrastructure. General economic development and political consensus is needed to reduce Africa's vulnerability to famine. In this context, judiciously provided foreign aid can be of immense help.